Christian Faith as Forgiveness - Calian, Carnegie Samuel (Theology today, 1981)
“To say that Christianity is Christ is to understand the Christian faith as forgiveness personified in Christ. Furthermore, this forgiveness centered in Christ has the power to humanize our existence.”